Analysis of brazilin and protosappanin B in sappan lignum by capillary zone electrophoresis with acid barrage stacking. Issue 24 (December 2013) - Lu, Yuanqi; Bai, Hong; Kong, Chunyan; Zhong, Hao; Breadmore, Michael C.
<x xml:space="preserve">Abstract</x> A method was developed to determine brazilin and protosappanin B in natural products by CE after acid barrage stacking. The optimum conditions were as follows: a BGE of 20 mM sodium tetraborate (pH 9.2) containing 6% v/v of methanol, hydrodynamic injection (0.5 psi, 65 s) followed by hydrodynamic injection of 150 mM citric acid (pH 2.3; 0.5 psi, 22 s), and separated with +25 kV. Under these conditions, brazilin and protosappanin B were separated with a sample‐to‐sample time less than 13 min and detection limits of 0.28 μg/mL and 0.15 μg/mL, respectively. The applicability of the developed method was demonstrated by the detection of brazilin and protosappanin in methanol extract of sappan lignum.